1989
DOI: 10.2136/sssaj1989.03615995005300050013x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Dissolved Organic Carbon Adsorption on Soil

Abstract: The subsurface transport of inorganic and organic contaminants may be strongly related to the movement of dissolved organic carbon (DOC) through a soil profile. A variety of soil chemical and hydrologic factors control the mobility of the DOC, which may enhance or impede the transport of the associated contaminants. In this study, the sources of DOC adsorption on two proposed waste‐site soils are defined, and the chemical mechanisms operative during the adsorption process are specified. Adsorption isotherms fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
341
2
8

Year Published

1992
1992
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 576 publications
(378 citation statements)
references
References 0 publications
27
341
2
8
Order By: Relevance
“…Solution pH may influence leaching of SOC, because pH affects the adsorption of SOC by soil particles. The adsorption of SOC by soil particles was reported to be maximum at pH 4.5 for a Tennessee soil (loamy, thermic Typic Paleudult) (Jardine et al 1989). In the present study, the pH of the leachate decreased over time in the Wabasso sand, which may have influenced the reduction in SOC leaching (Figs.…”
Section: Dynamics Of Soluble C Leachingsupporting
confidence: 47%
See 2 more Smart Citations
“…Solution pH may influence leaching of SOC, because pH affects the adsorption of SOC by soil particles. The adsorption of SOC by soil particles was reported to be maximum at pH 4.5 for a Tennessee soil (loamy, thermic Typic Paleudult) (Jardine et al 1989). In the present study, the pH of the leachate decreased over time in the Wabasso sand, which may have influenced the reduction in SOC leaching (Figs.…”
Section: Dynamics Of Soluble C Leachingsupporting
confidence: 47%
“…Jardine et al (1989) observed in a Tennessee soil (loamy, thermic Typic Paleudult) that SOC adsorption by soil decreased as the concentration of added SO 4 -2 increased, suggesting that anion exchange was a mechanism of the SOC desorption. Qualls and Haines (1991) reported that many of the compounds separated from SOC in forest soils were amino acids or had carboxylic function groups -compounds usually negatively charged at moderate to high pH.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The indigenous organic matter was reported to suppress the adsorption of DOC in the subsoil under forests (Jardine et al 1989). However, the amount of DOC retained was larger in the untreated subsoil column than in the subsoil columns without organic matter in the present experiment as described above (Tables 1 and 3).…”
Section: Discussionsupporting
confidence: 45%
“…Sorption and desorption exchange equilibria are determined by many factors, including soil mineralogy, organic carbon content, solution pH and sorption kinetics (Nodvin, Driscoll & Likens 1986;Jardine, Weber & McCarthy 1989). If the source of organic matter in the B horizon of Harp Lake soils is primarily the accumulation of leachates from the A and litter horizons, we may estimate magnitude of the sink for DOC by sorption.…”
Section: Sorptionmentioning
confidence: 99%